Computer-enhanced mapping of activation sequences in the surgical treatment of supraventricular arrhythmias. - Buckles DS; Harold ME; Gillette PC; Case CL; Crawford FA (Pacing & Clinical Electrophysiology, 1990)
Surgical treatment of accessory pathways and ectopic foci requires accurate information on the physical locations of the arrhythmogenic substrates. Although electrophysiology studies during cardiac catheterization frequently provide accurate and reliable data, the physical locations of the sites to be ablated must be verified in situ by electrical activity mapping. We have developed a microcomputer-based system that facilitates creation of electrical activity maps, supplanting the manual method formerly used. Signals produced by mapping and reference electrodes, as well as cardiac diagrams with grid coordinates and times, are presented on a monitor in formats that are easily interpreted by the surgeon and cardiologist. The system is rapid, accurate, and reliable, and has reduced the time required to localize conduction abnormalities from 30 to 45 minutes for the manual method, down to an average of 22 minutes per case. The system is simple to operate, requiring only minimal training. All of the components of the system are commercially available; no specialized hardware is required.